FUNGSI DAN MAKNA LINGGA DALAM AJARAN AGAMA HINDU - Suta, I Made (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
Hinduism is a religion that has given birth to a very complex culture in the field of astronomy, agricultural science, philosophy and other sciences. Likewise from this culture gave birth to worship facilities in the form of ancient relics, one of which was Lingga. Lingga is a symbol of fertility offered by the Indus valley civilization which is mainly associated with Shiva worship. Lingga can mean the manifestation of Lord Shiva which is described as Phalus which is usually placed above Yoni who describes men and women (Lingga-Yoni). The problem examined in this paper is how the function and meaning of Linga according to Hinduism in Indonesia. To answer these problems, data collection methods are used; literature studies, documents and observations and assisted with Religion and Symbol theory. Based on data data, it can be seen that the Lingga function is a religious function, namely strengthening, stabilizing Srddha Bhakti Hindus, then the function of fertility is by worshiping Lord Shiva through the media Lingga to invoke fertility on agriculture. Besides that, through worship Lingga has religious significance and symbolic meaning because Lingga is viewed from the religion as a symbol of worship before Lord Shiva. Lingga is believed to have magical powers so that Hindus draw closer to the presence of Ida Sang Hyang Widhi through the Lingga worship media in religious ceremonies such as piodalan in the Kahyangan Tiga / Jagat Temple. Symbolic meaning is Lingga as the symbol of Purusa (Akasa) and earth (Yoni) symbol of Pradana